2010
DOI: 10.1098/rstb.2009.0308
|View full text |Cite
|
Sign up to set email alerts
|

The principle of ‘maximum energy dissipation’: a novel thermodynamic perspective on rapid water flow in connected soil structures

Abstract: Preferential flow in biological soil structures is of key importance for infiltration and soil water flow at a range of scales. In the present study, we treat soil water flow as a dissipative process in an open non-equilibrium thermodynamic system, to better understand this key process. We define the chemical potential and Helmholtz free energy based on soil physical quantities, parametrize a physically based hydrological model based on field data and simulate the evolution of Helmholtz free energy in a cohesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
101
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 99 publications
(110 citation statements)
references
References 57 publications
(79 reference statements)
6
101
0
Order By: Relevance
“…The MEP principle emerges from the trade-off between thermodynamic "forces"/gradients and fluxes, because the latter depletes the former (Kleidon et al, 2006;Kleidon and Schymanski, 2008). Zehe et al (2009) recently showed that preferential pathways, when activated, are more efficient dissipators of Helmholtz free energy in cohesive soils, especially during dry summer conditions. Apparent preferential pathways offer additional degrees of freedom to the flow process and Zehe et al (2009) suggested that water flow in soils organises in such a way that dissipation of Helmhotz free energy becomes maximum (MED) for a given rainfall input, for a given soil and given soil structures.…”
Section: Ask the "Why-questions"mentioning
confidence: 99%
See 1 more Smart Citation
“…The MEP principle emerges from the trade-off between thermodynamic "forces"/gradients and fluxes, because the latter depletes the former (Kleidon et al, 2006;Kleidon and Schymanski, 2008). Zehe et al (2009) recently showed that preferential pathways, when activated, are more efficient dissipators of Helmholtz free energy in cohesive soils, especially during dry summer conditions. Apparent preferential pathways offer additional degrees of freedom to the flow process and Zehe et al (2009) suggested that water flow in soils organises in such a way that dissipation of Helmhotz free energy becomes maximum (MED) for a given rainfall input, for a given soil and given soil structures.…”
Section: Ask the "Why-questions"mentioning
confidence: 99%
“…This sudden change in behaviour manifests itself either in the form of an activity/triggering event as in the case of earthquakes (a hot spot in space as suggested by Rundle et al, 2006), or in the form of strongly increased reaction rates in biogeochemical systems (a hot moment in time as suggested by McClain et al, 2003), or as a qualitative change in the macroscopic dynamics as in the case of a laser (Haken, 1983). When the threshold is crossed, and associated processes or responses become considerably faster or slower, and/or the thermodynamic mixing is much more or much less efficient (Kleidon and Schymanski, 2008;Zehe et al, 2009). Examples of elementary threshold phenomena include phase transitions between the liquid, solid and gas phases of an element, or from laminar to turbulent flow, or from emission of normal light to laser light (Haken, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…To do so, the measurements, which were originally taken in 0.1 m increments, were resampled at depths by linear interpolation. Due to the potentially short correlation length of soil moisture (Zehe et al, 2010), inverse distance interpolation between two locations is generally not appropriate. In the case of the vertical profiles, however, the integration depths of the probes exceeded the measuring increments.…”
Section: Data Analysis 251 Tdr Data Analysismentioning
confidence: 99%
“…Zehe et al (2010) evaluate the effect of preferential flow associated with biogenic soil structures on hydrological fluxes using nonequilibrium thermodynamics. They show that these structures act to maximize dissipation of chemical potential gradients within the soil.…”
Section: Contents Of This Issuementioning
confidence: 99%